Computer-Assisted Versus Manual Planning for Stereotactic Brain Biopsy: A Retrospective Comparative Pilot Study. Issue 4 (5th August 2019) - Marcus, Hani J; Vakharia, Vejay N; Sparks, Rachel; Rodionov, Roman; Kitchen, Neil; McEvoy, Andrew W; Miserocchi, Anna; Thorne, Lewis; Ourselin, Sebastien; Duncan, John S
Abstract: BACKGROUND: Stereotactic brain biopsy is among the most common neurosurgical procedures. Planning an optimally safe surgical trajectory requires careful attention to a number of features including the following: (1) traversing the skull perpendicularly; (2) minimizing trajectory length; and (3) avoiding critical neurovascular structures. OBJECTIVE: To evaluate a platform, SurgiNav, for automated trajectory planning in stereotactic brain biopsy. METHODS: A prospectively maintained database was searched between February and August 2017 to identify all adult patients who underwent stereotactic brain biopsy and for whom postoperative imaging was available. In each case, the standard preoperative, T1-weighted, gadolinium-enhanced magnetic resonance imaging was used to generate a model of the cortex. A surgical trajectory was then generated using computer-assisted planning (CAP), and metrics of the trajectory were compared to the trajectory of the previously implemented manual plan (MP). RESULTS: Fifteen consecutive patients were identified. Feasible trajectories were generated using CAP in all patients, and the mean angle determined using CAP was more perpendicular to the skull than using MP (10.0° vs 14.6° from orthogonal; P  = .07), the mean trajectory length was shorter (38.5 vs 43.5 mm; P  = .01), and the risk score was lower (0.27 vs 0.52; P  = .03). CONCLUSION: CAP for stereotactic brain biopsy appears feasible and may be safer in selected cases.